Transcriptional Characteristics of IDH-Wild Type Glioma Subgroups Highlight the Biological Processes Underlying Heterogeneity of IDH-Wild Type WHO Grade IV Gliomas - Chang, Yu-Zhou; Li, Guan-Zhang; Pang, Bo; Zhang, Ke-Nan; Zhang, Xiao-Hui; Wang, Yong-Zhi; Jiang, Zhong-li; Chai, Rui-Chao (Frontiers in Cell and Developmental Biology, 2020)
IDH-wildtype diffuse gliomas, which have a poorer prognosis than their IDH-mutant counterparts, also accompany with high heterogeneity. Here, we aimed to identify the key biological processes associated with the three groups of IDH-wildtype diffuse gliomas in 323 patients. By the cIMPACT-NOW update 3 recommendation, the three groups are: Group A, diffuse astrocytic glioma, WHO grade II/III; Group B, diffuse astrocytic glioma, with one (or more) of the three genetic alterations: TERT promoter mutation, EGFR gene amplification, gain of chromosome 7 combined with loss of chromosome 10, WHO grade IV; and Group C, glioblastoma, WHO grade IV. Consistent with their histologic and genetic molecular features, we successfully identified that biological activities associated with “cell cycle” and “cell mitosis” significantly elevated in Group B compared with Group A; Microenvironment related hallmarks “Angiogenesis” and “Hypoxia”, and biological processes of “extracellular matrix”, “immune response”, and “positive regulation of transcriptional activities” were more enriched in Group C than Group B. We also constructed a 9-gene signature from differentially expressed genes among the three groups to further stratify the WHO grade IV gliomas (Group B and C) whose survival cannot be clearly stratified by current classification systems. This signature was an independent prognosis factor for WHO grade IV gliomas and had better prognostic value than other known factors in both training and validation dataset. In addition, the signature risk score was positively correlated with the amount of infiltrated immune cells, expression of immune checkpoints, and the genes enriched in biological processes of “immune response”, “cell cycle”, and “extracellular matrix”. The bioinformatic analysis results were also validated by immunohistochemistry and patient derived cells proliferation assay. Overall, our findings revealed the key biological processes underlying the newly classifications of IDH-wildtype diffuse glioma. Meanwhile, we constructed a signature which could properly stratify the prognosis, cell proliferation activates, extracellular matrix mediated biological activities, and immune-microenvironment of IDH-wildtype WHO grade IV gliomas.